Performalism : Form and Performance in Digital Architecture - Grobman, Yasha Jacob; Neuman, Eran (Routledge, 2012)
Today, with the advent of digital media technologies and the ability to conceptualize, express and produce complex forms using digital means, the question of the status of the architectural form is once again under consideration. Indeed, the computer liberated architecture from the tyranny of the right angle and enabled the design and production of non-standard buildings, based on irregular geometry. Yet, the questions concerning the method of form expression in contemporary architecture, and its meaning, remain very much open. Performalism takes up this discussion, defines it.